2023
DOI: 10.1002/ange.202218669
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cations Suppressing Proton Diffusion Kinetics for Electrocatalysis

Abstract: Proton transfer is crucial for electrocatalysis. Accumulating cations at electrochemical interfaces can alter the proton transfer rate and then tune electrocatalytic performance. However, the mechanism for regulating proton transfer remains ambiguous. Here, we quantify the cation effect on proton diffusion in solution by hydrogen evolution on microelectrodes, revealing the rate can be suppressed by more than 10 times. Different from the prevalent opinions that proton transport is slowed down by modified electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…This increase in FE is presumably achieved by the transport of potassium ions to the catalyst or the lower hydrophobicity of the electrode surface. While the latter could improve the aldehyde adsorption in catalyst layer, the presence of cations is known to suppress proton reduction [54,55].…”
Section: Screening Of Reaction Conditions In Flow Cellmentioning
confidence: 99%
“…This increase in FE is presumably achieved by the transport of potassium ions to the catalyst or the lower hydrophobicity of the electrode surface. While the latter could improve the aldehyde adsorption in catalyst layer, the presence of cations is known to suppress proton reduction [54,55].…”
Section: Screening Of Reaction Conditions In Flow Cellmentioning
confidence: 99%
“…This is attributed to the aggregation of cations in the outer Helmholtz plane, which hinders proton migration and hydrogen evolution reaction. 13,14 Additionally, the accumulation of cations enhances the local electric field intensity, promoting CO 2 adsorption and C−C coupling. 15,16 Furthermore, cations also exert a certain influence on the cathode catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, the alkaline metal cations present in the electrolyte have been proven to play a beneficial role in the electroreduction of carbon dioxide. This is attributed to the aggregation of cations in the outer Helmholtz plane, which hinders proton migration and hydrogen evolution reaction. , Additionally, the accumulation of cations enhances the local electric field intensity, promoting CO 2 adsorption and C–C coupling. , Furthermore, cations also exert a certain influence on the cathode catalyst. A study has indicated that the percentage of Cu in the surface oxidation state decreases with the increase of cation crossing: at high anode electrolyte concentration, only Cu 0 is present, whereas at low anode electrolyte concentration, both Cu 0 and Cu + coexist .…”
Section: Introductionmentioning
confidence: 99%